Laughing about Religious Authority—But Not Too Loud - Richter, Lena (Religions, 2021)
In Facebook groups of young Moroccan non-believers, cartoons, memes, and jokes that mock religion are widely shared. By phrasing the messages in a humorous way, it is possible to express experiences and viewpoints that are more difficult to communicate in direct speech. Studying these forms of humor can reveal several themes, frames, and tropes that are important to many former Muslims, such as criticizing the legal restrictions of non-belief and countering stereotypes about non-believers. This leads to the following question: To what extent is humor being employed as an (online) tool for young Moroccan non-believers to challenge the religious status quo? To answer this question, the article analyzes numerous examples of religious-related humor during the COVID-19 pandemic and Ramadan. Hereby, it becomes clear that many jokes remain a limited and covert dissent strategy, as they are only shared among fellow non-believers. Yet, this article argues that jokes are an important method of differentiation, self-expression, and in-group identification that can build a fruitful ground for future activism.